Harry Beamish using Foxboro recording thermometer in Dow Instrument Department - Dow Chemical Company (1948)
General view of instrument journeyman Harry Beamish inserting an element into a Foxboro recording thermometer in the Dow Chemical Company's Instrument Department. Established in 1926, the Instrument Department was responsible for the installation and maintenance of the assorted apparatus necessary to manage the plant's production facilities and processes. The department notably maintained accurate standards for temperatures, voltage, resistance, flow and pressures against which the plant's instruments were regularly calibrated and checked for accuracy.
Keywords: Employees; Industries; Scientific apparatus and instruments; Dow Chemical Company; Thermometers; Thermometers--Calibration; Beamish, Harry